Measurements of the velocity-field characteristic of indium phosphide - Hamilton, D; Hamilton, Douglas K (1979)
The thesis describes measurements of the velocity-field characteristic of indium phosphide, below threshold by a direct method and above threshold by domain measurements. Comparisons, with good agreement, are made with microwave measurements, below threshold on material from the same slices, and above threshold on material with very similar properties. A historical description of the Gunn effect and domain theory precedes a description of the structure of indium phosphide and a survey of published velocity-field calculations and measurements, showing the difference between 2- and 3-level conduction band models. A value for the T valley deformation potential has previously been deduced from the temperature variation of low-field mobility by adding reciprocal mobilities due to different scattering processes. This method is examined and experimental results of other workers are shown consistent with a lower deformation potential than supposed. Sub-threshold results agree closely with other, published, measurements, using various techniques. Extended to 77 K, the subthreshold method gave results agreeing reasonably with predictions for this temperature, and very well with extrapolations from other calculated and measured data. Published high-field domain measurements made with a pointcontact probe differ greatly from others. Experiments to produce a point-contact probe and associated differentiator with a known performance, and analysis of a simple circuit model indicate that the specimen resistivity controls the probe response, necessitating different probe resistances for different material resistivities. The probe was still found fundamentally difficult to use and is suspected of causing specimen damage due to localised heating under the point. Domain shapes measured agreed with published measurements from capacitive probes, but domain velocity was higher, giving a higher valley velocity (0.76 - 0.99 x 1O 7 cm/s). Comparison of the deduced velocity-field curve with published calculations strongly supports a 2-level transfer mechanism.